Olhares sobre a educação ambiental: uma proposta educacional entre uma das unidades do Colégio Tiradentes de Belo Horizonte e o Parque Estadual Serra Verde MG - Juliana Silvério Alves (2017)
This work investigates the planning and development of an educational proposal carried out in one of the units of the Tiradentes College of Belo Horizonte, in partnership with the Serra Verde State Park - MG. For this proposal, six activities were developed taking into account the critical perspective of Environmental Education (GUIMARÃES, 2000a), the three steps for School Environmental Education (SILVEIRA, 2002) and the Design Research methodology (PLOMP, 2009). The focus of the educational proposal was to encourage students to reflect critically on their social and environmental reality, with emphasis on the space they were inserted, which includes a State Park near the Tiradentes College of Belo Horizonte participating in the research and considering the relationship the local and global space. The educational proposal was applied by the researcher teacher during the 3rd stage of the academic year and in the Geography classes, in view of her training in this area of knowledge. It was developed with the students of the 9th year of elementary school. The classes were filmed and their records made in the field notebook and in the class mapping form, and the written assignments were also collected by the students. At the end of the application of the educational proposal, audiences of the semi-structured interviews were recorded with two monitors of the Serra Verde State Park - MG, in order to obtain their impressions about the partnership in the accomplishment of the educational proposal. Activity one was composed of a script with questions about the neighborhood that students were entering and should be answered from the search on internet sites and maps. In activity two students should choose a local water course to observe, outside the class time, and record the notes in the environmental assessment protocol, presenting in the classroom the photograph and the conclusion about the place visited. Activity three foresaw a field research that should be given to the researcher teacher about the history of the Serra Verde State Park - MG, its characteristics and environmental problems. Activity four consisted of a lecture given by the monitors of the Park in the College participating in the research, followed by a trail in the Park. Activity five brought texts about globalization and its impacts to the environment, which should be discussed in the classroom with the mediation of the researcher teacher. Lastly, Activity Six envisaged practical activities for the improvement of the College, the Park or other spaces around it. As a result, we found that in the activity one the students performed the requested task and participated in the proposed discussions. In activity two there was less involvement and some groups did not perform the activity as directed. We understand that the activity requires a greater time for its accomplishment, considering the complexity of the theme to be worked on. Activities three and four occurred according to plan and with high student participation. In activity five there was less involvement and when analyzing their characteristics, as well as their results, we understand that this activity did not complement, as planned, the set of activities. Activity six presented significant actions that were suggested and carried out by the students at the Tiradentes College of Belo Horizonte participating in the research and at the Serra Verde State Park - MG, corresponding to the activity objective. These results gave us more indications for the adequacy of the educational proposal to its objectives and the necessary subsidies for the improvement and organization of the product of this study. In this process of reworking the proposal, for a final product, we chose to extend the development time of activity two and exclude activity five.